A Remarkable Remission: Treating HMA Refractory Transforming MDS with Single-Agent Low-Dose Cytarabine Leading to an Ongoing Six-Year OS - David Palmer; Lydia Jones (Case Reports in Medicine)
Hypomethylating agents (HMA) are the standard of care for patients ≥65 years with intermediate-high risk myelodysplastic syndrome (MDS) unsuitable for intensive therapy or stem cell transplant (SCT). However, many patients will develop relapse/refractory disease, at which point limited treatment options remain. There has been a lot of research into investigational agents following HMA failure, especially now into targeted therapy, but there is no final consensus or convincing data to guide clinicians. Low-dose cytarabine (LDAC) has been in the armamentarium for some time, but the value of LDAC is judged differently by various guidelines. Nevertheless, in a subgroup of patients who fail on a HMA and wish to continue treatment, LDAC may still have the potential to improve overall survival (OS). In this case report, we present an 85-year-old gentleman with HMA refractory high-risk/transforming MDS (with a noncomplex karyotype) achieving an ongoing six-year OS with single-agent second-line LDAC. LDAC may therefore still be considered by clinicians as a therapeutic option, but when available, patients should be enrolled on a clinical trial.